Knowledge and Self-Efficacy Towards Eating Behaviors by People Living with Diabetes Mellitus - Sari, Lisa Anita; Astuti, Ani; Merdekawati, Diah (KnE Life Sciences, 2021)
Diabetes mellitus sufferers have metabolic issues caused by insulin disorders which indicate hyperglycemia. Behavior related to food and eating, including the amount of calories, dietary choices, setting a meal plan, and control dietary challenges are particularly important for diabetes mellitus sufferers owing to the impact of these measures on the speed with which blood glucose levels increase. With better understanding, diabetic patients can analyze their food intake and adopt appropriate eating behaviors. Self-efficacy can affect the patient’s commitment to their health. Knowledge and self-efficacy support healthy eating behavior patterns. This study aims to identify the relationship between knowledge and self-efficacy with regards to eating behaviors among people living with diabetes mellitus. Bandura’s promotion model was provided as a conceptual framework. A simple random sampling technique was used to recruit 201 participants with diabetes mellitus type 2. Data collection was via a Demographic Questionnaire, an Eating Behavior Questionnaire, a Diabetes Knowledge Questionnaire (DKQ), and a Diabetes Mellitus Self-Efficacy Questionnaire (DMSQ). Data was analysed using univariate and bivariate analysis. The results indicate that participants’ eating behavior, knowledge, and self-efficacy were at a low level. This study also indicated a significant relationship between knowledge (p < 0,000) and self-efficacy (p < 0,00) and eating behaviors. The results provide important information to suggests that community nurses should increase the knowledge about diabetes mellitus management and use self-efficacy to design effective intervention to promote healthy eating behavior to keep blood sugar in control. Keywords: eating behavior, knowledge, self-efficacy, diabetes mellitus